2011
DOI: 10.1111/j.1600-0528.2011.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

The risk of temporomandibular disorder in patients with depression: a population-based cohort study

Abstract: This study demonstrates that patients with depression are at an elevated risk of developing TMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
39
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 25 publications
9
39
1
4
Order By: Relevance
“…Spasm of the masticatory muscles is a painful symptom in TMD and is caused by muscle distension, contraction, or fatigue due to the presence of parafunctional habits such as bruxism and onychophagia (2,3,5). Several studies, in different populations, have shown that these habits are triggered or aggravated by emotional stress (2,(3)(4)(5)(6)(7)(8)(9)(10). Evidence indicates that myofascial pain and functional somatic syndromes such as fibromyalgia and chronic fatigue syndrome are comorbidities of the muscular pain that may be due to psychosocial factors.…”
Section: Introductionmentioning
confidence: 99%
“…Spasm of the masticatory muscles is a painful symptom in TMD and is caused by muscle distension, contraction, or fatigue due to the presence of parafunctional habits such as bruxism and onychophagia (2,3,5). Several studies, in different populations, have shown that these habits are triggered or aggravated by emotional stress (2,(3)(4)(5)(6)(7)(8)(9)(10). Evidence indicates that myofascial pain and functional somatic syndromes such as fibromyalgia and chronic fatigue syndrome are comorbidities of the muscular pain that may be due to psychosocial factors.…”
Section: Introductionmentioning
confidence: 99%
“…The studies, however, do not conclude whether TMD is a predisposing factor for depression, or depression predisposes the emergence of TMD. In a study, individuals with depression were 2.65 times more likely to develop TMD compared with the group without depression 26 . The use of RDC/TMD Axis II is considered a reliable and valid indicator of depression, somatization and psychosocial disorder in response to pain, because although it does not provide a psychiatric diagnosis, it gives initial scientific support to validate the clinical decision-taking based on evidence 17,18 .…”
Section: Resultsmentioning
confidence: 99%
“…Besides that, depression increases the perception of pain, which can be linked to the appearance of chronic symptomatology 27 and be predisposing factor for TMD. A study showed that individuals with depression presented 2.65 times more chances of developing TMD when compared to the group without depression 28 . Somatization on RDC/TMD is known as NSPS.…”
Section: Discussionmentioning
confidence: 99%